Pelaksanaan Hak-Hak Pasien Terhadap Pelayanan Tenaga Kesehatan di Rumah Sakit - Ningsih, Siska Ayu (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2020)
Patients as health service users certainly have rights that must be fulfilled by service provider facilities and by the health service personnel themselves. This study aims to see the implementation of patient rights to the services of health workers at the Regional General Hospital of M. Yunus Bengkulu. This research is a qualitative descriptive study. Informants who become sources of information are patients, nurses and doctors. Data obtained by in-depth interviews and observation. The results of the study found several related themes, namely; the implementation of the informed concent which becomes an obligation every time an action will be carried out, there are several obstacles in fulfilling the patient's rights, and several legal remedies that can be taken by the patient if there are defaults related to the fulfillment of patient rights. In conclusion, the patient's rights to obtain the best possible health care from health workers are still not optimal. The efforts of patients whose rights are not fulfilled or there is a violation that causes harm to the patient, patients can report complaints and will be followed up by the hospital. Suggestions, that health workers who provide health services can serve quickly because the patient may need immediate treatment, as well as the first treatment according to the patient's needs so that it can give confidence that the treatment received is started and carried out correctly.Keywords: Patient Rights, Hospital Services, Health Personnel